2012
DOI: 10.1103/physrevc.85.044611
|View full text |Cite
|
Sign up to set email alerts
|

Target-state dependence of cross sections for reactions on statically deformed nuclei

Abstract: As part of an effort to understand how neutron-induced reactions on excited states in deformed nuclei differ from those on ground states, we have carried out coupled-channels calculations of the angle-integrated cross sections on the ground and excited states of several actinide nuclei with differing K-values for the ground-state band (; 238 U, K = 0; and). Of particular interest is the compound-nucleus formation cross section. We find that the ratio of the excited to ground-state compound formation cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
6
29
0
Order By: Relevance
“…The largest difference is at most 0.7% seen in σ CN . Such a good agreement amongst different CC codes is also reported elsewhere [17]. Although we show the comparison at 100 keV only, in general the agreement is improved as the incident energy increases.…”
Section: Coupled-channels Optical Modelsupporting
confidence: 89%
“…The largest difference is at most 0.7% seen in σ CN . Such a good agreement amongst different CC codes is also reported elsewhere [17]. Although we show the comparison at 100 keV only, in general the agreement is improved as the incident energy increases.…”
Section: Coupled-channels Optical Modelsupporting
confidence: 89%
“…It was shown that the common practice of calculating neutron cross sections with three coupled levels in K = 0 + ground-state bands is inadequate [7]. This result was confirmed and generalized in a new comprehensive study by Dietrich et al [8], but none of these papers included additional vibrational bands in the coupling scheme of even-even nuclei or additional rotational bands in odd-A nuclei.…”
Section: Introductionmentioning
confidence: 93%
“…quantity for statistical reaction modeling. It has been shown that σ CN (E) strongly depends on employed coupled-channels couplings [8]. The proposed extension should account for multiple-band couplings, while keeping the achieved quality of description of the whole set of scattering data (e.g., total cross-section data above 5 MeV were described by the RIPL 2408 potential within the quoted experimental uncertainty of about 1.5%).…”
Section: Introductionmentioning
confidence: 99%
“…This was modeled using the ESGM level densities (with a 5% adjustment via the a-parameter), the Koning-Delaroche potential, and the MLO gamma strength function. Since the ground state deformation has a value of β 2 = 0.302, CC were invoked (a default number of four levels were coupled -the conclusions of [19] don't apply for charged particles subbarrier). Although [29] states that a CC approach gives enhancements in the transmission functions for both positive and negative Q-values subbarrier, probably due to the relatively small barrier a minimal overall improvement was observed in comparison to the absense of CC (graph of spherical case not shown).…”
Section: Se(pγ)mentioning
confidence: 99%
“…Seven collective levels were coupled following the prescription in ref. [19]. The parabolic representation of microscopically determined HFB fission barriers were used.…”
Section: Introductionmentioning
confidence: 99%